2020
DOI: 10.1177/0095798420957503
|View full text |Cite
|
Sign up to set email alerts
|

Africultural Coping Systems Inventory: Psychometrics in a Clinical Sample of African American Women

Abstract: The Africultural Coping Systems Inventory (ACSI) assesses African Americans’ culturally relevant stress coping strategies. Although its factor structure, reliability, and validity of the scores have been examined across ethnic groups of African descent persons, psychometric properties have not been investigated in an African American clinical sample. Thus, it is unclear if the ACSI is useful for research with African Americans with distress. To assess the ACSI’s psychometrics, we used data from 193 low-income … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 60 publications
0
4
0
Order By: Relevance
“…We purposely chose a coping scale with a strong theoretical underpinning based on research into culturally preferred coping practices for Black individuals, but the scale has rarely been used in studies of Black adults who experienced trauma. However, in a recent study of Black women who had experienced recent trauma, Watson‐Singleton et al 43 found the instrument psychometrics were different than in the initial validation study. This psychometric difference suggests the ACSI may perform differently for women who experience trauma compared with other groups of Black adults.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…We purposely chose a coping scale with a strong theoretical underpinning based on research into culturally preferred coping practices for Black individuals, but the scale has rarely been used in studies of Black adults who experienced trauma. However, in a recent study of Black women who had experienced recent trauma, Watson‐Singleton et al 43 found the instrument psychometrics were different than in the initial validation study. This psychometric difference suggests the ACSI may perform differently for women who experience trauma compared with other groups of Black adults.…”
Section: Discussionmentioning
confidence: 94%
“…Ritual‐Centered Coping (3 items, scores 0‐9) includes performing rituals (eg, “Lit a candle for strength or guidance in dealing with the problem”). The ACSI has been used with African American women of all ages, including trauma victims 43 and college students 19,44 . Cronbach's α have been .60 to .90 45,46 …”
Section: Methodsmentioning
confidence: 99%
“…Several studies have found that proactive coping (e.g., active problem solving) helps to mitigate the harmful effects of discrimination on health outcomes among Black Americans [ 12 , 14 ]. African-centered forms of coping, such as participation in prayer and meditation, seeking support from family and friends, and connecting with culturally sanctioned social groups and community resources, are commonly used by Black Americans to cope with stress [ 15 17 ], including those living with HIV [ 25 , 43 ]. However, this study may be the first to examine whether Africultural coping methods mitigate the harmful effect of discrimination on ART adherence, thereby acting as a moderator of the association between discrimination and adherence.…”
Section: Discussionmentioning
confidence: 99%
“…Little research has examined the effects of culture-specific coping strategies commonly used by Black Americans to manage chronic stress from exposure to discrimination. African-centered coping strategies commonly used by Black Americans include spiritual practices and rituals (e.g., prayer, meditation, incense burning), support seeking from family and friends, and accessing culturally sanctioned social groups and community resources [ 15 17 ], which reflect West African coping principles such as spirituality, collectivism, and communalism [ 18 , 19 ]. Findings have been mixed regarding whether the use of these strategies relate to levels of reported stress [ 20 ], and whether their use may serve as a buffer against the negative effects of discrimination on health outcomes [ 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%